Negative Effects of a Nonhost Proteinase Inhibitor of ~19.8 kDa from Madhuca indica Seeds on Developmental Physiology of Helicoverpa armigera (Hübner) - Jamal, Farrukh (Hindawi Publishing Corporation, 2014)
An affinity purified trypsin inhibitor from the seed flour extracts of Madhuca indica (MiTI) on denaturing polyacrylamide gel electrophoresis showed that MiTI consisted of a single polypeptide chain with molecular mass of ~19.8 kDa. MiTI inhibited the total proteolytic and trypsin-like activities of the midgut proteinases of Helicoverpa armigera larvae by 87.51% and 76.12%, respectively, at concentration of 5 µg/mL with an IC(50) of 1.75 µg/mL against trypsin like midgut proteinases. The enzyme kinetic studies demonstrated that MiTI is a competitive inhibitor with a K (i) value of 4.1 × 10(−10) M for Helicoverpa trypsin like midgut proteinases. In vivo experiments with different concentrations of MiTI in artificial diet (0.5, 1.0, and 1.5% w/w) showed an effective downfall in the larval body weight and an increase in larval mortality. The concentration of MiTI in the artificial diet to cause 50% mortality (LD(50)) of larvae was 1.5% w/w and that to cause reduction in mass of larvae by 50% (ED(50)) was 1.0% w/w. Nutritional indices observations suggest the toxic and adverse effects of MiTI on the growth and development of H. armigera larvae. The results suggest a strong bioinsecticidal potential of affinity purified MiTI which can be exploited in insect pest management of crop plants.